PENGEMBANGAN DAN IMPLEMENTASI LITERASI DIGITAL UNTUK MENANGKAL HOAKS KEBENCANAAN DI CIANJUR - Agustinah, Aminah; Nasution, Sri Mulyani; Rahmat S., Asep Deden; Andriani, Astri Dwi; Teguh, Dody Faraitody (LPPM Universitas Nusa Mandiri, 2024)
The flood of information following the earthquake disaster in Cianjur has had an impact on the spread of hoaxes which is difficult to stop. The impact not only causes anxiety and fear, it even triggers division and conflict. To educate the public in preventing hoaxes, the Volunteer Team from Putra Indonesia University and Jayabaya University for three months after the earthquake carried out activities to Strengthen Digital Literacy and Psychosocial Assistance at earthquake victim posts spread across Cianjur. Implementation of community service uses a service-learning method that adapts the learning system to the situation and needs of the community. Community service activities are carried out using teaching aids that can be received by earthquake victims in the form of fun-learning with a duration of two hours. The first session is filled with introductions and storytelling, then learning while playing in the second session. The group was divided into two separate locations, namely the children's group and the parents' group. The aim is for each group to receive different material reinforcement according to their individual needs. Implementation of activities is carried out in collaboration with various parties (between universities, company CSR and local stakeholders). The results of the activities carried out showed that participants were able to understand digital culture, ethics in using social media, and the Personal Data Protection Law.